Ремифологизация милитарного: малая проза участников фантастического конвента 2019 года - Karpov, Denis (Wiener Slawistischer Almanach, 2024)
The article is devoted to modern military Russian prose. Based on the collection of fantastic stories #Zhividonbass, the analysis of the main components of the myth of war is carried out, typical structures on the basis of which the narrative is built are revealed. It is concluded that the stories of the collection repeat the motifs of Soviet military literature, and their fantastic component plays only the role of a setting for different forms of military ideologies.